2011
DOI: 10.1002/hlca.201100252
|View full text |Cite
|
Sign up to set email alerts
|

Photo‐Cross‐Linking of Polymethacrylates with Stilbene Chromophores in the Side Chains

Abstract: Methacrylates (¼ 2-methylpropenoates) 5 with (E)-stilbene (¼ (E)-1,2-diphenylethene) building blocks on tethers of variable length were prepared (Scheme 2) and polymerized (i.e., 5 ! 6; Scheme 3) in the presence of AIBN (¼ 2,2'-azobis(2-methylpropanenitrile). 4-[(E)-2-Phenylethenyl]phenyl acetate (7) as model compound established the cyclodimerization as a single irreversible photoreaction. i.e., (7 ! 8 -11; Scheme 4) in the absence of oxygen. The solution photolysis of the polymers 6 provided a similar result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Recently we reported on polymethacrylates with (E)-stilbene chromophores in the side chains [9]. Similar results were obtained for stilbenoid dendrimers some years ago [10].…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…Recently we reported on polymethacrylates with (E)-stilbene chromophores in the side chains [9]. Similar results were obtained for stilbenoid dendrimers some years ago [10].…”
Section: Introductionsupporting
confidence: 80%
“…Although the number of (E)-stilbene units in the copolymer chains was much lower than in the homopolymers [9], the irradiation in solution (CH 2 Cl 2 or C 6 H 6 , λ ≥ 300 nm) led predominantly to intrachain reactions to give 7a, b (Scheme 3). The corresponding [2π + 2π] photocycloaddition worked very well for 3a-6 and 3b-1, 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of photo-cross-linking is increased by the aromaticity of the side chain that silk possesses in abundance. Consequently, stilbene can be a good cross-linker for silk fibroin (24,26). We found that a solution containing 0.02 M of stilbene led to the most rapid rate of cross-linking.…”
mentioning
confidence: 84%
“…UVC light induces [2π + 2π] cycloadditions between the stilbene units, whereas the radicals generated in the silk tethers undergo dityrosine bonding (for details, see Supporting Information and Fig. S1) (24,25). The rate of photo-cross-linking is increased by the aromaticity of the side chain that silk possesses in abundance.…”
mentioning
confidence: 99%